PENERAPAN TEKNIK CARD AND APRECIATION DAPAT MENINGKATKAN MOTIVASI APRESIASI DAN PRESTASI SISWA DALAM PEMBELAJARAN PENDIDIKAN SENI - priyo utomo (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
Learning using the techniques and Pin Card Application was a part of the teaching model of cooperative learning in a small group and for students who argued rewarded with pin. The result showed that there was a percentage increase in the number of active students who appreciate/ found either in the first cycle and the second cycle, the first cycle in the first meeting was on average of 67.6% and the second meeting was on average 76.7%, so an increase of 9.6% and in the first meeting of the second cycle an average of 77.3% and the second meeting on average 83.0%, so an increase of 6.3%. The results of the analysis of daily tests indicated that there was an increase of the students’ achievement that was the first cycle an average of 71.39 and absorption of students in the second cycle in the average of 78.82 of the students’ absorption, so that the increase in the students' absorption of 7.43. This classroom action research had proved that with the application of techniques and Apreciation Card could enhance the students' appreciation, achievement, and motivation in Art Education of the seventh graders of the first state yunior high school of Lamongan.